INORGANIC AND ORGANIC SOIL PHOSPHORUS FRACTIONS IN HUMID TROPICAL TEA PLANTATION OF WEST BENGAL, INDIA - HARISADHAN MALAKAR; DEBJANI GHOSH; SOUROV CHATTERJEE; ABHIJIT DEBNATH (The Bioscan, 2015)
Inorganic (Pi) and organic phosphorus (Po) fractions were studied in some soils of humid tropical tea gardens of West Bengal, India. In particular, Po fractions were estimated following a cheaper and routine method involving differential solubility of organic P compounds to acidic/alkaline extractants. Because of strong acid reaction of soils calcium phosphate fraction was less (7.11% of total P) than the iron and aluminium phosphates and these moderately labile inorganic P constituted 28.23-171.9 mg kg”1 (mean 76.18) of 422.6-1231mg kg”1total P in these soils. Reductant soluble P (22.09% of total P) was found the major fraction among all Pi fractions in soils. Among organic fractions moderately resistant fulvic P (45.66% of Po) was highest varying from 90.07 to 219.3 mg kg”1, followed by non-labile humic acid P (28.6%of Po).Microbial P (LPm) was strongly correlated (P<0.001) with the total labile P suggesting the role of biological cycle in the labile pool of Po in these tea garden soils. It was estimated that a minimum of 9-28 kg of phosphate might have supplied by the soil resource itself to the growing crops which corresponded to 36-100% of phosphate removed by tea from the soil ha”1 year”1.